From "Noma Kumnyama" to "Pata Pata": a history - Allingham, Rob (International Library of African Music, 2009)
Miriam Makeba's 1967 recording of "Pata Pata" represents the commercial apex of this iconic artist's long career. For over forty years, the record has enjoyed a high profile, international popularity thanks to continual radio airplay, ongoing physical sales and more recently, internet downloads, both paid-for and unpaid. However, "Pata Pata" is not without its own historical and structural anomalies, for it is in fact a combination of two separate original melodies derived from two completely different sources. The first eight bar melodic phrase in "Pata Pata" comes directly from an earlier song entitled "Noma Kumnyama" (Zulu: "Even If It's Dark") by the Dundee Wandering Singers, an mbube group led by Alson Novemu Mkhize.
Keywords: African Music